AKTIVITAS FRAKSI ETIL ASETAT KULIT BUAH JERUK NIPIS (Citrus aurantifolia (Christ) Swing) SEBAGAI ANTIPIRETIK PADA MENCIT YANG DIINDUKSI VAKSIN DPT - Satrio Wibowo Rahmatullah; Eka Fitri Susiani; Muhammad Reza Fahlevi; Guntur Kurniawan; Siti Nurhaliza Leyla (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Lime (Citrus aurantifolia (Christm.) Swing) is one of the types of oranges containing elements of compounds that are beneficial, so widely used as traditional medicine. This research aims to know the antipyretic activity of ethyl acetate fraction peel of lime. Phytochemical screening test result fraction ethyl acetate lemon rind contains flavonoids, saponins, alkaloids and essential oils. Total of 25 mice were divided into 5 groups, group I negative control, group II positive control, group III,IV,V were given ethyl acetate fraction at a dose of 0,07%/gBW,, 0,105%/gBWand 0,14%/gBW. Based on the results of graph average temperatures decrease the dose that the third has antipyretic activity because it can lower the temperature and the largest decreased in temperature at a dose 0,14%/gBW. Based on the test result ANOVA obtained sig. value 0,000. which means there is a temperature difference of meaning between 5 group treatment. And on Independent Test Sample T-test between a positive control with a dose 0,14%/gBW the value of sig. 0,601 (> 0,05) which means there is no meaningful difference.